Cultural landscape conservation: a technical valuation in rural fishing village in Johor, Malaysia - Ismail, Nor Atiah; Mohd Tahir, Osman; Sujak, Siti Shahirah; Mohd Yunos, Mohd Yazid; Ariffin, Noor Fazamimah; Ismail, Sumarni; Utaberta, Nangkula (AENSI Publisher, 2015)
Background: Cultural landscape is a symbiosis and an understanding of a situation where man co-exist and cherish the relationship binding him with natural environment that is rich with ecological balance. This relationship is expressed usually by the rural landscape in which we live. Sustainable bond between man and nature forms the landscape of the rural residential area as a humble and peaceful setting with verdant forest and vegetation; which is shared by the whole community. Objectives: This paper investigates the meaning of cultural landscape and conservation effort of rural cultural landscape and its responsiveness in a village namely Kong Kong Village, Johor, located in the South part of Malaysia. Results: Research and landscape proposal discussed in this paper provides an example of cultural landscape planning and design that is not only able to empower the local identity and values, but also injecting potential to increase local communities income while preserving their eco cultural landscape values. Conclusion: Cultural landscape conservation is crucial in the current technological and modernization world. All human beings are associated with the place where they originated. Living intact with culture and history enabled our future generations to reach the sky; without forgetting their land of origins.